(untitled) (Theatrum historiae, 2012)
The main aim of the study is to present various interpretations of the controversial treatise by Vuk S. Karadžič “Kovčežič za istoriju, jezik iobičaje Srba sva tri zakona” and also to demonstrate the cultural, linguistic and social conditions of its origin. An important factor of the analysis is the problem of national historiographies, more specifically of the Serbian and Croatian historiographies. This document is considered from defensive or hegemonistic and aggressive or even Great-Serbian positions. One of the main motifs of the treatise is the question of why Vuk Karadžič created the postulate on stocav definition of the Serbian nationality. There are four interpretation variants at our disposal. The first possibility is that Vuk Karadžič consciously increased the number of Serbs to the detriment of Croats and Bosnian Muslims or Slav Muslims in the Ottoman Empire. We may also consider the fact that Vuk Karadžič to some extent adopted the ideas of prominent European Slavicists (Kopitar, Šafárik, Dobrovský and others). The ethnic diversity within the military borders could also have influenced him. His document could also have been a sort of defence against the growing Croatian nationalism and efforts to acquire the cultural legacy of Dubrovnik on the part of the Croatians. However, at the same time an equivalent process was taking place with the Serbs in the region of Dalmatia.